Pengontrol Kualitas Air Tambak Menggunakan Metode Fuzzy Logic untuk Budidaya Udang Windu - Poerwanto, Edy; Rasmana, Susijanto Tri; Wibowo, Madha Christian (Journal of Control and Network Systems, 2014)
Some fish farmers have done a shrimp pond water circulation and turning water wheel, so as to keep the pond water conditions. Fish farmerâs waterwheel turned on at all times, while for the water pump turned on when they found floating shrimp. This method would impact on growth shrimp can be detrimental to the shrimp. So monitoring and controlling the conditions of pond water pond water is continuously required to maintain water quality monitoring and process control pond. This system uses sensors temperature and pH as inputs the system, whereas for the actuator system using water mill, tap lime, and water pump. By using the pH sensor and temperature monitoring and process control an advanced water quality better. Actuators waterwheel, tap lime, and water pumps can alter water quality becomes better. By using tap lime and water pump changes the normal acid pH 7.2 6.65 can be reached within 14 minutes. While the use of the water wheel can change the temperature of 39 Â° C to 32 Â° C in less than 16 minutes. Thus this system can facilitate farmers to anticipate significant changes in water quality, so that the fish farmers will get maximum results at harvest time.